The material world - Cotterill, Rodney 1933-2007 (Cambridge University Press, 2008)
Using the cosmos as a backdrop, Rodney Cotterill delivers a fascinating journey of Nature's materials, from the atom to the living organism. This is a beautifully illustrated, expanded account of the highly praised Cambridge Guide to the Material World. The author seamlessly blends the physics, chemistry and biology of Nature, portraying matter with all its elegance and flaws. Although the book is divided into material types, the author connects concepts and pinpoints commonalities between the inorganic and organic domains. It challenges the reader to question our structured view of the world and whether this limits our scientific endeavour, aptly demonstrated by the new chapter devoted exclusively to the mind. Through the breadth of topics and engaging prose, this book will act as a superb introduction to material science for students and those intrigued by the material world we live in